Cysteamine Chemisorption at Mercury-Solution Interfaces in the Context of Redox and Microdissociation Equilibria - Dorčák, Vlastimil; Kroutil, Ondřej; Kabeláč, Martin; Janata, Jiří; Vacek, Jan (Langmuir, 2024)
The redox behavior and chemisorption of cysteamine (CA) at a charged mercury surface are described, with an emphasis on its acid-base properties supported by molecular dynamics and quantum mechanical calculations. It was found that CA forms chemisorbed layers on the surface of the mercury electrode. The formation of Hg-CA complexes is connected to mercury disproportionation, as reflected in peaks SII and SI at potentials higher than the electrode potential of zero charge (p.z.c.). Both the process of chemisorption of CA and its consequent redox transformation are proton-dependent. Also, depending on the protonation of CA, the formation of typical populations of chemisorbed conformers can be observed. In addition, cystamine (CA disulfide dimer) can be reduced on the mercury surface. Between the potentials of this reduction and peak SI, the p.z.c. of the electrode used can be found. Furthermore, CA can serve as an LMW catalyst for hydrogen evolution. The mechanistic insights presented here can be used for follow-up research on CA chemisorption and targeted modification of other metallic surfaces.